Massive Star Modeling and Nucleosynthesis - Ekström, Sylvia (Frontiers in Astronomy and Space Sciences, 2021)
After a brief introduction to stellar modelling, the main lines of massive star evolution are reviewed, with a focus on the nuclear reactions from which the star gets the needed energy to counterbalance its gravity. The different burning phases are described, as well as the structural impact they have on the star. Some general effects on stellar evolution of uncertainties in the reaction rates are presented, with more precise examples taken from the uncertainties of the \cago\ reaction and the sensitivity of the $s$-process on many rates. The changes in the evolution of massive stars brought by low or zero metallicity are reviewed. The impact of convection, rotation, mass loss, and binarity on massive star evolution is reviewed, with a focus on the effect they have on the global nucleosynthetic products of the stars.